68Ga-PSMA PET/MR–Positive Peritoneal Metastasis in the Falciform Ligament in Recurrent Prostate Cancer. (August 2017) - Kranzbühler, Benedikt; Tran, Sébastien; Zilli, Thomas; Burger, Irene A.
Abstract : Abstract: Synchronous or metachronous metastases develop in approximately one third of all prostate cancer (PCa) patients. Main sites of metastasis include lymph nodes, bone, lung and liver. Secondary peritoneal carcinomatosis is very rare in PCa, with only a few published cases. 68 Ga-PSMA PET–based imaging is a promising tool for staging and restaging PCa. We report a case of 68 Ga-PSMA PET/MR–positive peritoneal metastasis as site of primary relapse after definitive PCa treatment in a 58-year-old man with a prostate-specific antigen of 30 ng/mL at time of the study. Exploratory laparoscopy and subsequent histopathologic examination confirmed nonascitic peritoneal PCa carcinomatosis.